THE INFLUENCE OF WORK ENVIRONMENT, WORK CULTURE ON THE QUALITY OF PUBLIC SERVICES AT DPPKUM CITY OF MAGELANG - Laras Tri Utami; Joko Tri Nugraha; Matheus Gratiano Mali (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze the influence of the work environment and work culture on the quality of public services at the Department of Trade, Industry, Cooperatives and Micro Enterprises (DPPKUM) of Magelang City. The study used a quantitative explanatory research approach with a sample of 93 employees selected by proportional random sampling. Data were collected through Likert scale questionnaires and observations, then analyzed using multiple linear regression analysis. The results showed that the work environment had a significant negative effect on the quality of public services (B = -0.489, t = -2.969, p = 0.004), the results of work culture did not have a significant effect (B = 0.115; t = 0.584; p = 0.561). However, simultaneously both variables had a significant effect on the quality of public services (F = 4.623; p = 0.012; R² = 0.093).